The Effect of Unihemispheric Concurrent Dual-Site Transcranial Direct Current Stimulation of Primary Motor and Dorsolateral Prefrontal Cortices on Motor Function in Patients With Sub-Acute Stroke - Achacheluee, Sahar Toluee; Rahnama, Leila; Karimi, Noureddin; Abdollahi, Iraj; Arslan, Syed Asadullah; Jaberzadeh, Shapour (Frontiers in Human Neuroscience, 2018)
It is believed that unihemispheric concurrent dual-site transcranial direct current stimulation (tDCSUHCDS) of the primary motor cortex (M1) and the dorsolateral prefrontal cortex (DLPFC) causes an increase in motor cortex excitability. However, the clinical effect of this type of stimulation on patients with neurological conditions is not yet known. The aim of the present study was to assess the effect of anodal-tDCSUHCDS (a-tDCSUHCDS) on upper limb motor function in subacute stroke patients. Fifteen patients participated in this sham-controlled crossover study. The main outcome measures were the reaction time (RT) to visual stimuli, completion time of a nine-pin pegboard (9-PPB), and the scores from the Fugl–Meyer assessment (FMA) for the upper limb of the involved side before and after three brain stimulation conditions. For a-tDCSUHCDS, the anodal electrodes were placed on the M1 and the DLPFC, while for a-tDCS, the anodal electrode was placed on the M1. For the sham stimulation, the tDCS was turned off after 30s. For brain stimulation, the selected current was 1 mA for 20 min. After a-tDCSUHCDS, there was a significant reduction in the RT and completion time of the 9-PPB compared with the times after a-tDCS and the sham stimulation: p = 0.013 and p = 0.022, respectively). However, there was no significant difference in the FMA scores after the three types of stimulations (p = 0.085). Compared with a-tDCS, a-tDCSUHCDS temporarily improved the RT and dexterity of the involved hand in subacute stroke patients. Trial registry: IRCT2015012520787N1 http://apps.who.int/trialsearch/Trial3.aspx?trialid=IRCT2015012520787N1